The oxidation states of niobium and tantalum in mantle melts - Burnham, A; Berry, A; Wood, B; Cibin, G (2012)
Niobium K-edge and tantalum L III-edge XANES spectra were recorded for silicate glasses quenched from melts equilibrated at oxygen fugacities (in log units relative to the iron-wüstite buffer) ranging from IW+6.7 to IW-4.3 at 1400-1650°C and atmospheric pressure to 1.5GPa. Niobium and tantalum were found to occur exclusively as Nb 5+ and Ta 5+. This suggests that changes in oxidation state do not contribute to the fractionation of Nb from Ta in arc settings or the generation of the hidden Nb-rich reservoir that is necessary to explain the deviation of the Nb/Ta ratio of the bulk silicate Earth from the chondritic value. © 2012 Elsevier B.V.